Modern analytical chemistry in archaeology and arts: An overview - Kuss, H.; Telgheder, U.; Bader, N.; Zimmermann, B. (Libyan Journal of Science &Technology, 2022)
The relationship between analytical chemistry, arts, and archaeology and the role of the analytical techniques in archaeology and arts have been discussed. The analytical techniques have been divided and listed into sample destructive and non-destructive techniques. Each technique has been discussed briefly